A hybrid transient CFD-thermoelectric numerical model for automobile thermoelectric generator systems. (15th February 2023) - Luo, Ding; Yan, Yuying; Li, Ying; Wang, Ruochen; Cheng, Shan; Yang, Xuelin; Ji, Dongxu
Graphical abstract: Based on the proposed hybrid transient CFD-thermoelectric model, we analyzed the dynamic response characteristics of an automobile thermoelectric generator (TEG) system under a complete driving cycle. Highlights: A hybrid transient CFD-thermoelectric numerical model is proposed for the first time. Dynamic output power keeps in a smoother change trend than exhaust temperature. Steady-state analysis overestimates output power and underestimates conversion efficiency. Conversion efficiency can be enhanced by periodic exhaust waste heat. Abstract: Dynamic performance prediction of the automobile thermoelectric generator system is one of the research hotspots in the field of thermoelectric technology. In this work, a hybrid transient CFD-thermoelectric numerical model is proposed for the first time to predict the dynamic response characteristics of an automobile thermoelectric generator system. Taking the exhaust gas of a heavy truck under a highway fuel economy test driving cycle as the transient heat source, the transient numerical study on the automobile thermoelectric generator system is carried out. It is found that the dynamic output power of the automobile thermoelectric generator system changes more smoothly than exhaust temperature due to the effect of thermal inertia, while the conversion efficiency fluctuates greatly. The transient output power at t  = 467 s and transient conversion efficiency at t  = 635 s reach the highest values of 45.16 W and 39.68 %, respectively. Within the period of 765 s, the total power generation and average conversion efficiency of the automobile thermoelectric generator system are 26460 J and 3.29 %, respectively. Through the transient experimental validation, the average error of transient output voltage between experimental and model results is 6.43 %. This work fills the gap in the dynamic performance prediction of thermoelectric devices used for fluid waste heat recovery. The findings are helpful in better understanding the dynamic response characteristics of the automobile thermoelectric generator system.